A Comparison of Cyber-Security Oriented Testbeds for IoT-Based Smart Grids - Gunduz, Muhammet Zekeriya; Das, Resul (Ieee, 2018)
Combining conventional power networks and information communication technologies forms smart grid concept. Researches on the evolution of conventional power grid system into smart grid continue thanks to the development of communication and information technologies hopefully. Testing of smart grid systems is usually performed in simulation environments. However, achieving more effective real-world implementations, a smart grid application needs a real-world test environment, called testbed. Smart grid, which is the combination of conventional electricity line with information communication technologies, is vulnerable to cyber-attacks and this is a key challenge improving the smart grid. The vulnerabilities to cyber-attacks in smart grid arise from information communication technologies' nature inherently. Testbeds, which cyber-security researches and studies can be performed, are needed to find effective solutions against cyber-attacks capabilities in smart grid practices. In this paper, an evaluation of existing smart grid testbeds with the capability of cyber security is presented. First, background, domains, research areas and security issues in smart grid are introduced briefly. Then smart grid testbeds and features are explained. Also, existing security-oriented testbeds and cyber-attack testing capabilities of testbeds are evaluated. Finally, we conclude the study and give some recommendations for security-oriented testbed implementations.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: IoT; smart grid; testbeds; cyber security; privacy